Dr. Behzad Farokhi — Deep Plane Facelift — Tehran - Farokhi, Behzad (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Behzad Farokhi, practicing in Tehran, Iran. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003113; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; iran; tehran